Key Success Factors for Organizations in Controlling Employee Turnover - Desi Aryati Sulastri; Veithzal Rivai Zainal; Azis Hakim (Jurnal Indonesia Sosial Sains, 2025)
This study aims to identify the factors that influence employee turnover and to explore effective strategies to control it. Employee turnover, which refers to the permanent resignation of employees either voluntarily or involuntarily, can significantly disrupt organizational operations and hinder goal achievement, especially when involving competent and high-performing staff. A descriptive analysis method was employed, with data collected through a literature review from academic books, journal articles, and research reports related to employee turnover. The findings reveal that key factors contributing to turnover include weak organizational culture, low job security, limited career advancement, insufficient recognition and benefits, lack of work flexibility, and poor work-life balance. If not managed properly, these factors can lead to increased dissatisfaction and voluntary resignation. The study highlights that organizations must proactively implement comprehensive retention strategies, such as competitive compensation, transparent career development paths, supportive leadership, and flexible work arrangements. The implications of this study suggest that by addressing these areas, organizations can reduce turnover rates, enhance employee satisfaction, and foster long-term organizational success and stability.